Personality Traits, Psychological Distress, and Locus of Control among Drug Abusers and Non-Drug users: Personality Traits, Psychological Distress and Locus of Control - Anwar, Zoha; Arzeen, Naeema; Arzeen, Saima; Muhammad, Hayat (Pakistan Journal of Health Sciences, 2023)
The problem of drug addiction is growing day by day in Pakistani youth. Previous studies on drug addictions highlighted that drug addicts have different personality traits and level of stress, anxiety and depression as compared to the non addicts. Objective: To get the deep understanding of the personality traits, psychological discomfort, and Locus of control among drug and non-drug users. Methods: For this purpose, a sample of 200 participants, drug abusers (n=100) and non-drug users(n=100) of the same age, were taken from the general population and various rehabilitation facilities in Islamabad and Rawalpindi by using three reliable scales: The TIPI Questionnaire, the DASS-21, and the Locus of Control Questionnaire were administered to the selected sample. The core findings of the study were interpreted in terms of descriptive, correlation and t–test analysis. Results: The study findings demonstrate a statistically significant difference between drug and non-drug users in extraversion, Openness to experience, agreeableness, conscientiousness, and emotional stability. Drug abusers reported significant levels of psychological discomfort and external Locus of control, in contrast to non-drug users who scored well on internal Locus of control. Conclusions: Drug users exhibits high level of psychological discomfort and negative personality trait than non-drug users. Therefore, health professionals and psychologists working in drug addiction rehabilitation centers should focused on the improvement of drug addicts’ psychological health.